Microgels of hydrophobically modified-ethyl hydroxy ethyl cellulose (HM-EHEC) with 5-flurouracil for drug delivery applications - Wali, Ashwini; Badiger, Manohar (Research Journal of Biotechnology, 2025)
The polysaccharides (e.g. celluloses and proteins) which form the basic building blocks of life, are gaining increased interest in recent times for researchers to develop newer health care products from renewable bio-polymers which are cheaper and easily available with different desirable properties. Gels are highly swollen three dimensional networks of hydrophilic polymers cross-linked by physical or chemical interactions. Our focus was to design and develop a novel microgel system which would effectively deliver the anti-cancer drug to the targeted site by slow and sustained release for longer times. The water soluble hydrophobically modified ethyl hydroxy ethyl cellulose (HM-EHEC) biopolymer was used in the synthesis of microgels by Michael-type addition reaction between the primary hydroxyl groups of HM-EHEC and Divinyl sulphone (DVS) crosslinker using water-in-oil emulsion technique. The microgels obtained were spherical in shape having flower type morphology with average size of 5 to 8 μm. The anti-cancer drug 5-Flurouracil (5-FU) drug was successfully incorporated and around 56% of the 5-FU was released in 72 hours with a loading efficiency of 95%. The cell viability (MTT assay) studies confirmed the cycto-toxicity on the MDA-MB 231 breast cancer cell line. There was an increase in the cell death with increase in the concentration of microgel containing drug concentration. The HM-EHEC microgels could be effectively used in the form of a topical cream in the skin and breast cancer for on-site slow and targeted delivery.